Safety profiles and effects of Tualang honey on the levels of inflammation bone markers and oestradiol in breast cancer patients - Zakaria, Zaida (2018)
Honey is traditionally used among breast cancer patients in Malaysia with the belief that it can improve the overall health. However, to our knowledge, no study has reported on the effects of Tualang honey supplementation on safety profiles, inflammatory markers, bone markers and estradiol among breast cancer patients. The aim of this study was therefore, to determine safety profile, and effects of Tualang honey on inflammatory markers, bone markers, and on oestradiol among breast cancer patients. A randomised controlled-trial was conducted on breast cancer patients who were treated with anastrozole and recruited from Oncology Clinic, Universiti Sains Malaysia. The patients were randomised into control and honey groups. Honey group was supplemented with 20 g/day of Tualang honey for 12 weeks. Blood was collected at pre- and post-interventions to evaluate the safety profiles, and levels of inflammatory markers, bone markers and oestradiol between and within the groups. At pre-intervention, haemoglobin, interleukin-6 and carboxyterminal crosslinked telopeptide of type 1 collagen (CTX) levels were significantly higher, whereas procollagen type 1 amino-terminal propeptide (P1NP) level was significantly lower, in control group compared to honey group. There were no significant differences found for all parameters between two groups at postintervention after adjustment for confounding factors. In control group, levels of albumin, alanine aminotransferase, creatinine, interleukin-1 beta, tumour necrosis factor alpha and CTX at post-intervention (after 12 weeks), were significantly higher compared to their corresponding levels at pre-intervention. In honey group, at postintervention (after 12 weeks) total white blood cell count, platelet count, creatinine and P1NP levels were significantly higher whereas CTX level was significantly lower compared to their corresponding levels at pre-intervention. However, no significant differences were found for oestradiol levels between and within groups. In conclusion, the intervention which consists of 20 g daily honey supplementation to breast cancer patients for 12 weeks was significantly safe, prevented the increased inflammation, reduced bone resorption and increased bone formation without changes in estradiol level. These beneficial effects are probably through the action of phenolic compounds present in Tualang honey which had antioxidant, antiinflammatory and anticancer properties. These findings may suggest the beneficial effects of honey supplementation on inflammation and bone among breast cancer patients treated with anastrozole and the potential use of honey as an adjuvant therapy. However, further studies are required to elucidate the exact mechanism of action on these beneficial effects of Tualang honey and monitoring of those parameters is recommended for longer honey intake.